2021
DOI: 10.1186/s13287-021-02526-z
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial stem/progenitor cells and their roles in immunity, clinical application, and endometriosis

Abstract: Endometrial stem/progenitor cells have been proved to exist in periodically regenerated female endometrium and can be divided into three categories: endometrial epithelial stem/progenitor cells, CD140b+CD146+ or SUSD2+ endometrial mesenchymal stem cells (eMSCs), and side population cells (SPs). Endometrial stem/progenitor cells in the menstruation blood are defined as menstrual stem cells (MenSCs). Due to their abundant sources, excellent proliferation, and autotransplantation capabilities, MenSCs are ideal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 173 publications
1
57
0
Order By: Relevance
“…The risk factors of endometriosis may involve: 1) women's age; 2) heavy but short menses [7]; 3) low body mass index [13]; 4) psychological and emotional factors; 5) stress and/a pain response in pelvis; 6) nulliparity; 7) high education and social level [3]. Patients with endometriosis have a high risk for systemic comorbidities including autoimmune, cardiovascular and atopic diseases.…”
Section: Etiology and Pathogenesis Of Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors of endometriosis may involve: 1) women's age; 2) heavy but short menses [7]; 3) low body mass index [13]; 4) psychological and emotional factors; 5) stress and/a pain response in pelvis; 6) nulliparity; 7) high education and social level [3]. Patients with endometriosis have a high risk for systemic comorbidities including autoimmune, cardiovascular and atopic diseases.…”
Section: Etiology and Pathogenesis Of Endometriosismentioning
confidence: 99%
“…Although the pathogenesis of endometriosis is still debated, evidence indicates that both the onset and the progression of this disease are supported by: 1) an imbalance of invasive, proliferative and adhesive properties of endometrial cells; 2) increased production of inflammatory molecules [1]. Currently, the most accepted theory seems to be Sampson's retrograde menstruation hypothesis, which suggests that during menstruation, endometrial fragments migrate through the Fallopian tubes to the peritoneal cavity and reach the peritoneum, as they are able to attach, survive, and implant in different locations (Fallopian tubes, ovaries, and pouch of Douglas) [2,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Basic science experts reiterate the importance of an exhaustive and undirected characterization of the cells before their application ( Galipeau and Sensebe, 2018 ). However, several studies have already shown the regenerative, reparative, and protective properties of eMSCs and recently also of MenSCs ( Chen et al., 2019 ; Kong et al., 2021 ).…”
Section: Cellular Properties Of Menscs: Reparative Regenerative and Protective Effectsmentioning
confidence: 99%
“…Taken together, MenSCs have a variety of effects on both the innate and specific immune responses that have been extensively reviewed ( Bozorgmehr et al., 2020 ; Kong et al., 2021 ) and are not the focus of this study. They show inconsistencies between in vitro and in vivo findings and a considerable variation among experimental models, needing further investigation to identify the underlying mechanisms that organize the dialogue that MenSC use to modulate the immune system.…”
Section: Cellular Properties Of Menscs: Reparative Regenerative and Protective Effectsmentioning
confidence: 99%
See 1 more Smart Citation